Increased CD11/CD18 expression on the peripheral blood leucocytes of patients with HIV disease: relationship to disease severity. - Palmer, S (1993)
In HIV disease increased adhesion between leucocytes themselves and between leucocytes and endothelium may contribute to cell loss and viral spread. Using a novel method for the preparation of blood leucocytes for flow cytometry, we report increased expression of leucocyte adhesion molecules (LeuCAMs) (CD11/CD18) on peripheral blood leucocytes of patients with HIV disease compared with normal controls. Patients were divided into two groups on the basis of CD4 T lymphocyte numbers (those with > 0.5 x 10(9)/l and those with < 0.2 x 10(9)/l), and assessed for p24 antigen expression, viral load and serum tumour necrosis factor (TNF) levels as well as LeuCAM expression. Patients with < 0.2 x 10(9)/lCD4 cells had more p24 antigen and more HIV infectious virus and more serum TNF than those with > 0.5 x 10(9)/l. Whilst the percentages of only monocytes and polymorphs expressing CD11b were significantly increased in patients with the least CD4 cells, the density of LeuCAMs, expressed as mean fluorescence intensity (MFI), was significantly increased on all leucocytes, with the most significant increases being seen on patients with the fewest CD4 T cells. Our findings are consistent with leucocyte activation by a soluble factor, although we could find no correlation between levels of TNF and LeuCAM expression. The increased expression of adhesion molecules on peripheral blood leucocytes could play a role in the cellular extravasation and aggregation seen in HIV disease.